2006
DOI: 10.1111/j.1467-8624.2006.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and Secrecy in Adolescent–Parent Relationships

Abstract: Beliefs about parents' legitimate authority and adolescents' obligations to disclose to parents and actual disclosure and secrecy in different domains were examined in 276 ethnically diverse, lower middle-class 9th and 12th graders (Ms=14.62 and 17.40 years) and their parents (n=249). Adolescents were seen as more obligated to disclose prudential issues and less obligated to disclose personal than moral, conventional, and multifaceted issues; parents viewed adolescents as more obligated to disclose to parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
589
6
13

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(676 citation statements)
references
References 54 publications
61
589
6
13
Order By: Relevance
“…First, they emerged when controlling for perceived disclosure (Finkenauer et al, 2002;Finkenauer & Hazam, 2000;Larson & Chastain, 1990;Smetana et al, 2006). In the present study, we assessed secrecy and concealment by asking marital partners to rate the extent to which they thought their partner concealed information from them.…”
Section: Perceiving Concealment In Close Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, they emerged when controlling for perceived disclosure (Finkenauer et al, 2002;Finkenauer & Hazam, 2000;Larson & Chastain, 1990;Smetana et al, 2006). In the present study, we assessed secrecy and concealment by asking marital partners to rate the extent to which they thought their partner concealed information from them.…”
Section: Perceiving Concealment In Close Relationshipsmentioning
confidence: 99%
“…They found that both mothers and fathers who perceived their child to conceal information from them were less satisfied with their relationship with their child and less responsive to their child's needs. These associations held even when controlling for perceived disclosure, suggesting that secrecy and disclosure can be simultaneously present in a relationship (Finkenauer et al, 2002;Frijns, Finkenauer, Vermulst, & Engels, 2005;Smetana et al, 2006). To illustrate, when telling Mary about his new colleague, John may disclose her qualifications, what she said, and what her background is.…”
Section: Perceiving Concealment In Close Relationshipsmentioning
confidence: 99%
“…The level of adolescents' disclosure was found to differ between various domains. Adolescents disclose more about school-related topics Mother-Adolescent Agreement 4 and less about peers or personal issues, and they disclose more information to mothers than to fathers (Smetana et al 2006). We used probably the most renowned conceptualization of children's disclosure -that developed by Kerr and Stattin (2000).…”
Section: Mother-adolescent Agreement On Child Disclosurementioning
confidence: 99%
“…Third, we only focused on a very specific area of disclosure in adolescents' lives -school and spare time -so the results may differ for other contexts, as adolescents disclose different issues depending on the domain (Smetana et al 2006). Moreover, we only focused on two specific outcomes: conflicts and depressive symptoms.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation